Characterization of patients with Systemic Inflammatory Response Syndrome - Santaya López, Rolando; Cecilia Paredes, Eduardo Enrique; Echevarría Cruz, Ángel; Guillen Cánovas, Ana Mercedes; Echevarría Martínez, Luis Enrique (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
Introduction: Sepsis is an important health problem, considered the main cause of death worldwide in pediatric ages. Objective: to clinico-epidemiologically characterize children with systemic inflammatory response syndrome in the intensive care service of the Pediatric Provincial Teaching Hospital “Pepe Portilla Pinar del Río, from January 2020 to December 2021. Method: observational, descriptive and transversal research. A universe of 118 patients was studied in its totality. The information was extracted from medical records. Descriptive statistical methods were used. Results: Children under 5 years of age and males accounted for 58.5% and 52.5% respectively. Admissions came similarly from the emergency department and hospital wards. Sixty-seven.8 % arrived in the early stages, of which 82.2 % were community-acquired infections. The respiratory tract was the most frequent site of infection with 55.9%. Only 7.5 % of the children were malnourished. Exclusive breastfeeding was not maintained until the sixth month of life in 70.6 % of the children. Mortality was low (10.2 %), with patients admitted in severe sepsis and severe septic shock stage having the highest mortality. Conclusions: The number of admissions in sepsis stage is decreased in the study, especially in advanced stages with lower mortality, which contributed to the low mortality rate in the province.